Redução automatizada de redes de petri baseada em algoritmos genéticos - Bevilaqua, André (Universidade Federal de São Carlos, 2014)
Petri Net (PN) is a graphical mathematical tool used to create models that provide a formal specification of systems, creating the possibility of running behavior analysis and property verification. PN models can be used to model several system types, for example, Manufacturing Systems. In general, using PN to model systems with too many characteristics cause the so-called state-space explosion problem, in other words, a great element profusion in the model. In order to mitigate the referred problem researchers developed reduction rules to synthetize models. Reduced models maintain original system properties and can be easily analyzed and simulated. A method to automate reduction rules application is proposed on the present research. A Genetic Algorithm heuristic is responsible for applying six reductions rules on Place-Transition Petri Nets given as input. The proposed algorithm, presented as a Matlab toolbox, may contribute when simulating and running property verification methodologies on Petri Net models.
Keywords: Redes de computação; Sistemas de manufatura; Computação evolutiva; Redes de Petri; Algoritmo genético; Aplicações de manufatura; Petri net; Genetic algorithm; Manufacturing system; Petri net reduction; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO